The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fnbeh.2018.00088
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Chronic Ethanol Exposure From Adolescence to Adulthood Induces Cerebellar Neuronal Loss and Motor Function Damage in Female Rats

Abstract: Over the last years, heavy ethanol consumption by teenagers/younger adults has increased considerably among females. However, few studies have addressed the long-term impact on brain structures’ morphology and function of chronic exposure to high ethanol doses from adolescence to adulthood in females. In line with this idea, in the current study we investigated whether heavy chronic ethanol exposure during adolescence to adulthood may induce motor impairments and morphological and cellular alterations in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 44 publications
(72 reference statements)
1
29
0
Order By: Relevance
“…Variations any alteration in cerebellar mass. [4] No change in absolute cerebellar mass or cerebello-somatic index (absolute cerebellum weight / body weight) was also observed in the current study (data not shown). Even in chronic exposure, Et was ineffective to alter the brain weight while body weights were significantly less compared to control animals.…”
Section: Biochemical Parametersupporting
confidence: 52%
See 3 more Smart Citations
“…Variations any alteration in cerebellar mass. [4] No change in absolute cerebellar mass or cerebello-somatic index (absolute cerebellum weight / body weight) was also observed in the current study (data not shown). Even in chronic exposure, Et was ineffective to alter the brain weight while body weights were significantly less compared to control animals.…”
Section: Biochemical Parametersupporting
confidence: 52%
“…[5] Along with other brain regions, cerebellum faces neuronal loss in chronic Et exposure and this may have a relationship with loss of cognitive and motor functions. [4,6,7] In fact, compared to cerebral cortex, Et-induced apoptosis was higher in cerebellum. [8] Cerebellum, per se, is highly vulnerable to chronic Et exposure; nevertheless, the extent of damage depends on the profile of the subject as well as level of consumption.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In this test, the animal’s ability to maintain postural stability was evaluated [ 70 , 71 , 72 ]. Animals with impaired motor coordination and equilibrium are unable to perform descent and ascent movements on a bar with a slope greater than 45°.…”
Section: Methodsmentioning
confidence: 99%